2021
DOI: 10.3389/fnins.2021.783361
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Isocitrate Dehydrogenase 1 Genotype and Cell Proliferation in Gliomas Using Multiple Diffusion Magnetic Resonance Imaging

Abstract: Objectives: To compare the efficacy of parameters from multiple diffusion magnetic resonance imaging (dMRI) for prediction of isocitrate dehydrogenase 1 (IDH1) genotype and assessment of cell proliferation in gliomas.Methods: Ninety-one patients with glioma underwent diffusion weighted imaging (DWI), multi-b-value DWI, and diffusion kurtosis imaging (DKI)/neurite orientation dispersion and density imaging (NODDI) on 3.0T MRI. Each parameter was compared between IDH1-mutant and IDH1 wild-type groups by Mann–Whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 42 publications
1
1
0
Order By: Relevance
“…Previous studies reported ADC values could effectively evaluate the grades, proliferation activity, and tumor cell density of glioma [ 40 , 41 ]. In this study, ADC min , ADC mean , rADC min , and rADC mean are all negatively related to Ki-67 LI, which is consistent with prior studies [ 19 , 20 ]. In addition, among the four indicators, rADC min has the highest predictive efficiency on the Ki-67 index level, with an AUROC of 0.778.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Previous studies reported ADC values could effectively evaluate the grades, proliferation activity, and tumor cell density of glioma [ 40 , 41 ]. In this study, ADC min , ADC mean , rADC min , and rADC mean are all negatively related to Ki-67 LI, which is consistent with prior studies [ 19 , 20 ]. In addition, among the four indicators, rADC min has the highest predictive efficiency on the Ki-67 index level, with an AUROC of 0.778.…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, there could be potential correlations between ADC values and Ki-67 LI. Prior studies have reported that the ADC values of glioma are negatively correlated with Ki-67 LI [ 19 , 20 ]. However, due to the heterogeneity of glioma, especially glioblastoma, the ADC values within glioma are uneven, so it is necessary to standardize the ADC values within the tumor to obtain more reliable results.…”
Section: Introductionmentioning
confidence: 99%